Biofertilizantes: identificação das barreiras regulatórias e propostas para viabilizar esse insumo agrícola - Moraes, João Guilherme Vanzella (2015)
The focus of this research study is to identify bottlenecks in the Brazilian legislation that regulate biofertilizers by means of a revision of the main rules, acts and normative instructions of the sector, and to propose measures that facilitate its development. Inputs are part of the Brazilian legislation since the publication of the first Fertilizer Law in 1980; its uses are also described in academic publications. However the lack of registration of biofertilizer products at the Ministry of Agriculture, Livestock and Food Supply (MAPA) until the end of 2014 requires immediate attention from the input sector, its leaders and legislative figures. Understanding the implication and effects of the current legislation towards the adoption of the input, as well as the implications of the revision of norms and regulations present in this work, will support the input sector, political leaders and research bodies to adequate norms and technical procedures that enable the registration of solutions for the biofertilizer sector and that facilitate the access to biofertilizers by farmers. This study has revised the Brazilian legislation relevant to the biofertilizer input, interviewed political leaders, institutional leaders and prominent figures of private companies about the main challenges for the development of the sector. It also investigated the situation of the biofertilizer sector in other countries such as Canada, the Unites States and countries of the European Union through the revision of laws and relevant documents, and by means of interviews conducted with professionals of the input sector and representative institutions present in the markets mentioned above. Although there are differences in the definitions proposed by the various countries and other corresponding categories, the difficulties faced by companies of the nutrition sector to register biofertilizers is consistent to the efforts of US companies to create the biostimulant class, and to those of the majority of the European countries analyzed. It was identified that the current legislation and its interpretation and the requirements to launch new products do not fully comply with the needs of the biofertilizer producing sector. The biofertilizer sector does not have the same regulatory expertise found in the crop protection sector in order to better define validation protocols with the responsible authority. Changes in legislation, better articulation among the production chain and greater interaction with the Ministry of Agriculture, Livestock and Food Supply (MAPA) are essential to secure the viability of the biofertilizer input. Keywords: biofertilizers, legislation, inputs.